Investigating the Stability of Ru-promoted Fe-based Fischer-tropsch Catalyst at high Synthesis Gas Conversion. (November 2016) - Fraser, Ian; Rabiu, Ademola M.; van Steen, Eric
Abstract: The productivity of an iron-based Fischer Tropsch (FT) process strongly depends on the synthesis gas conversion. However, iron is known to oxidize significantly at high CO conversion due to the high reactor water partial pressures. In commercial iron-based FT plant this necessitate operation at low single pass conversion, resulting in high separation and recycling cost of the tail gas and the overall economics of the process. Ruthenium has been reported to demonstrate significant stability in the presence of water, hence the employment of FT catalyst promoted with Ru is expected to permit high CO conversion. In this study the stability of an industrial Fe-based FT catalyst impregnated with ruthenium is investigated. The reactions were carried out at industrially relevant conditions in a 1 dm 3 slurry reactor at 250 °C and 20 bar. It was noted that the Fe promoted with Ru was more stable at high CO conversion implying a significant resistance to deactivation in the presence of water. An increase in CO2 and CH4 selectivity and a fall in C5+ selectivity were also noted.